Angiotensin converting enzyme (ACE) activity levels in insulin-independent diabetes mellitus and effect of ACE levels on diabetic patients with nephropathy - Üstündag, B; Canatan, H; Cinkilinc, N; Halifeoglu, I; Bahcecioglu, IH (Wiley, 2000)
Involvement of complications is considered to be one of the major factors in the prognosis of diabetes mellitus (DM). Recent studies indicate that most diabetic complications such as nephropathy and hypertension are vascular-originated, Renin-angiotensin involvement, especially changes in ACE activity level, is considered to be a key factor since ACE converts angiotensin I to angiotensin II which is a potent vasoconstrictor and plays a vital role in the regulation of blood pressure. Our present study focused on ACE activity levels along with blood glucose and HbA(1c) levels in diabetic patients with (n = 18) or without (ii = 25) nephropathy as compared to control subjects (n = 25), Blood glucose levels were significantly higher in both diabetic groups compared to controls (p < 0.001). On the other hand. compared to controls, blood HbA(1c) levels were slightly higher in DM patients without complications whereas they were significantly increased in nephropatic DM patients (p < 0.001). There was a very strong increase (p < 0.001) at the level of ACE activity in both of the diabetic groups (with nephropathy: 47.11 +/- 3.70 U l(-1); without complications: 43.72 +/- 2.93 U l(-1): controls: 25.15 +/- 2.30 U l(-1)). ACE activity levels were also significantly higher in diabetic patients with nephropathy than in type II DM patients without complication (p < 0.01). Our results demonstrate that ACE activity levels are increased in diabetic patients. Additional significant increase in ACE activity levels in diabetic patients with complications such as nephropathy supports the hypothesis that ACE activity has an essential role in the development of complications in diabetes, Copyright (C) 2000 John Wiley &: Sons, Ltd.
Keywords: angiotensin converting enzyme (ACE); diabetes mellitus (DM); nephropathy